Mechanical tests for bituminous mixes : characterization, design and quality control - RILEM International Symposium (4th : 1990 : Budapest, Hungary); Fritz, A. W.; Eustacchio, E.; The International Union of Testing and Research Laboratory for Materials and Structures; RILEM Technical Committe 101-BAT (Bitumen and Asphalt Testing) (London : Chapman and Hall, 1990)
09